AL- ṬAḤĀWĪ’S METHOD TOWARDS THE VARIETY OF QIRAĀT IN TAFSIR AḤKĀM AL-QUR’ĀN AND ITS IMPLICATION TO ISTINBĀṬ AL-AḤKĀM
The variety of Qiraāt is closely related to the interpretation of the Quran. Often, variety of Qiraāt result in different understanding and law. Al-Tahāwī gives special attention on the variety of Qiraāt and its use in the istinbāṭ of fiqh rulings in his interpretation entitled Ahkām al-Qur’ān al-Karīm. This research aims at investigating al-Tahāwī’s method towards the variety of Qiraāt and its implication in the istinbāṭ of fiqh rulings. This research paper employs analytic descriptive method by exploring and analyzing the variety of Qiraāt included in the interpretation entitled Ah